COLORING THE SOUL: THE USE OF SPLIT BATIK ART IN EMOTIONAL THERAPY FOR PEOPLE WITH MENTAL DISORDERS (ODGJ) - Ristya Rini, Denik; Soesanto; Lestari, Wahyu (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2025)
ODGJ (People with Mental Disorders) are individuals who have mental disorders that can affect their way of thinking, feeling and behavior. ODGJ are identical with unstable emotions, therefore they need activities that can accommodate their emotions. Through creative activities, it is hoped that it can be a place for them to express themselves. Batik splash is known for its free and expressive coloring technique. The creative process of batik splash is free and not bound by any rules. This batik splash work activity is very suitable for pouring out emotions for individuals. Based on this background, creative activities are used as emotional therapy for ODGJ. This activity is a creative process that is integrated into a therapy program to help ODGJ express emotions and overcome stress. This study involved an ODGJ group who participated in an eight-week batik splash learning session. The results showed that the activity of creating batik splash not only improved motor skills and creativity, but also contributed to improving the emotional well-being of participants. Through qualitative analysis, it was found that participants felt more able to express themselves and experienced a decrease in symptoms of anxiety and depression. These findings indicate that splash batik art can be an effective therapeutic tool in supporting the mental health of ODGJ, as well as providing new insights into the application of art in a therapeutic context. This article will inspire mental health practitioners and art activists to develop innovative and impactful therapy programs.